Tursun Fakı’nın Cumhur-Name adlı eserinin metni ve incelemesi - Yazıcı, Neslihan (My University, 2005)
VII ABSTRACT The aim of this work is to give information about the differences between the work named Cumhurname which was written by Tursun Fakih and its versions. Cumhurname is a gazavatname that was written in form of mesnevi. At the end of the comparisons it is determined that this work is composed of one thousand four hundred and seventy three verses. The introduction explains the life of Tursun Fakih, his literary life and his other works. The language, the form, the subject and the characters of the work have been studied in the following parts. There is also an extensive

of the work before the text. After that the work is transcibed and translated into modern Turkish. A dictionary of old Turkish words has been prepared for the sake of readers. There is also index about the names of characters and places. At the end of the study the other versions of the work are added and sources are stated.
Keywords: Divan Şiiri; Edebiyat; Osmanlıca edebiyat; Osmanlıca şiir (Divan şiiri); Türk Edebiyatı